Internalizing rules. - Paulson, Spencer (Philosophy & Phenomenological Research, 2024)
The aim of this paper is to give an account of what it is to internalize a rule. I claim that internalization is the process of redistributing the burden of instruction from the teacher to the student. The process is complete when instruction is no longer needed, and the rule has reshaped perceptual classification of the circumstances in which it applies. Teaching a rule is the initiation of this process. We internalize rules by simulating instruction coming from someone else. Running these simulations enables us to toggle between the perspective of the instructor and our own perspective. By doing this we coordinate our perspectives with that of the teacher. The account given here provides a deeper explanation of why internalizing a rule involves the dispositions and reactive attitudes proponents of Rule Consequentialism often say it does, why moral reflection is variably demanding, how intergenerational moral progress is made possible by our cognitive architectures, and why the adoption of a rule should be understood in terms of teaching that rule.